SISTEM MONITORING KUALITAS AIR TAMBAK UDANG BERBASIS INTERNET OF THINGS (IOT) - Achmad Zamzami; Odis Fransisco; Irwan Irwan; Muhammad Iqbal Nugraha (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
At this time many vaname shrimp ponds have been made and developed, especially in the Bangka Belitung Islands. One of the main problems in shrimp ponds is the quality of pond water which must be in accordance with the living needs of shrimp, the process of monitoring water quality in shrimp ponds is usually done manually by taking water samples and then taking them to the laboratory for analysis. The purpose of this study is to facilitate farmers in the process of monitoring the water quality of shrimp ponds based on the Internet of Things (IoT). This research method is carried out by collecting data, designing control circuits, testing, and analyzing data. The average percentage error from the temperature test data for 1 hour is 0.31%, for 2 hours is 0.14%, and for 3 hours is 0.23%. The average percentage error from the pH test data for 1 hour is 3.05%, for 2 hours is 6.62%, and for 3 hours is 4.23%. The average percentage error of the salinity test results for 1 hour is 2.68%, for 2 hours is 4.27%, and for 3 hours is 1.95%.